Creation Alternative Energy Electronic Student Worksheets (E-LKPD) Based on the "Nabuang Sarok" Waste Management Program to Improve Students Environmental Concern - Febby Putri Iryanto; Festiyed Festiyed; Hamdi Hamdi; Selma Riyasni (Physics Learning and Education, 2025)
Through the use of online graphic design platform CANVA and waste management programs, this study seeks to create electronic student worksheets to enhance students environmental awareness using Model Problem Based Learning on alternative energy. The ASSURE model, which includes the development stage, is applied uses the Research and Development methodology. At SMA Negeri 8 Padang, observations the school environment and needs analysis involving 1 physics teacher and 28 students were conducted as part of the analysis stage. Based on these initial observations, it was found that students' environmental awareness was still low. In addition, students understanding of alternative energy was quite limited because digital teaching materials had not been fully utilized. Based on these identified problems, digital student worksheets on waste management programs were created to boost environmental awareness using the Model PBL. By using the Kappa Moment, the product feasibility validity test test conducted by three physics lecturers confirmed the content, language, presentation, and graphics were valid. Revisions were made based on their feedback. Based on results, it was shown the electronic student worksheet on alternative energy based on the waste management program "Nabuang Sarok" is appropriate to use, especially in the independent curriculum, to improve students' environmental awareness.